Sistema integrato per la localizzazione dei mezzi operativi dei Consorzi di Bonifica - De Pietri, Stefano; Liviero, Giuseppe (GEOmedia, 2009)
An integrated system for reclamation consortiums operational vehicles positioning The Valli Grandi and Medio Veronese italian reclamation consortiums have been testing the use of a GPS positioning system applied to operational vehicles. The information gathered through these tests highlight the importance of a quick intervention in critical or dangerous situations related to the operation of such vehicles. This article features the results, the shortcomings and the costs of this test with the aim of being useful to organizations operating in similar fields.